(5-tert-Butylporphyrinato)copper(II), a nonplanar porphyrin with only one sterically demanding meso residue - SENGE, MATHIAS (My University, 2011)
The title compound, [Cu(C24H20N4)], is a rare example of a porphyrin carrying only one substituent. Its crystal structure exhibits two molecules in the asymmetric unit. The bulky meso tert-butyl residue gives rise to a nonplanar macrocycle with significant ruf and sad distortions. As a result of the position of the substituent, the conformational effects are unsymmetric and to a significant extent localized in the affected quadrant of the macrocycle. In line with results for highly substituted nonplanar porphyrins, comparison with a free base and a nickel(II) complex shows that the conformation of the macrocycle is modulated via additional metal effects.
PUBLISHED
Keywords: porphyrin